Morphology and phylogeny reveal a novel species, Tolypocladium phycosomatis (Ophiocordycipitaceae, Hypocreales), from Yunnan, China - Li, Song-Yu; Lu, Ying-Ling; Zhao, Jing; Ma, Jin-Mei; Yang, Shi-Dao; Yu, Zhi-Yong; Yu, Hong (Phytotaxa, 2025)
Tolypocladium is classified within family Ophiocordycipitaceae. We formally describe and illustrate a novel species, Tolypocladium phycosomatis using morphological features and phylogenetic analyses. This new species was discovered in Yunnan Province, China. Phylogenetic analysis based on ITS, nrSSU, nrLSU, tef-1α, rpb1, and rpb2 gene sequences revealed that this species clustered closely with T. ovalisporum, forming a sister relationship. A comprehensive phylogenetic tree of the genus Tolypocladium was reconstructed, providing a foundation for further phylogenetic studies of this genus and its related taxa. This discovery enhances our understanding of species diversity within the genus Tolypocladium and provides a robust taxonomic foundation for their rational development and sustainable utilization.